FACTOR ASSOCIATED WITH LOW BACK PAIN COMPLAINTS IN TAILOR : LITERATURE REVIEW - Nurjannah, Besse; Tosepu, Ramadhan ((Jurnal Ilmiah Mahasiswa Kesehatan Masyarakat), 2024)
Background: An individual whose occupation is sewing is required to assume sedentary positions perform repetitive tasks while utilizing a single type of muscle. Sewing requires sharp concentration, coordination of posture and movements, and proper posture Method: Literature review A literature review was conducted using electronic data, specifically an original search of five periodicals. An electronic literature search is conducted utilizing databases such as PubMed and Google Scholar. "Lower back pain factor" and "low back pain in tailors" are the keywords utilized. Results of Research / Discussion: Extending one's work hours to the point of burnout is a direct consequence of the workload's difficulty. Muscle fatigue can result from an excessive burden; eventually, symptoms or discomfort may manifest in the affected areas. There are numerous approaches that can be taken to reduce or eliminate fatigue, beginning with time management and the work environment. When working in an inconvenient position, adhering to applicable regulations regarding leisure and working hours can significantly increase the amount of energy required for work. Conclusion: an examination of the literature encompassing five articles reveals that numerous factors contribute to the occurrence of low back pain complaints. These factors include seating position and attitude, burden, and work attitude. Keywords : Low Back Pain, Working Time, Workload and Body Posture